1996
DOI: 10.1063/1.116843
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of InAs–GaAs quantum dots subjected to high temperature annealing

Abstract: Annealing at higher temperature (700 °C) of structures with two-dimensional and three-dimensional arrays in InAs–GaAs quantum dots (QDs) results in an increase in the size and in a corresponding decrease in the indium composition of the QDs. The change in the In composition is monitored by the contrast pattern in the plan-view transmission electron microscopy (TEM) images viewed under the strong beam imaging conditions. Increase in the size of the QDs is manifested by the plan-view TEM images taken under [001]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(67 citation statements)
references
References 14 publications
7
60
0
Order By: Relevance
“…This, however, seems to remain in contradiction to some experimental observations regarding energies of the optical transitions reported by different authors, concerning, for instance, the InAs/ GaAs WL QWs. [9][10][11][12][13][14][15][16] They are very similar in many reports and are usually in satisfactory agreea͒ Author to whom correspondence should be addressed; electronic mail: grzegorz.sek@pwr.wroc.pl ment with the calculations assuming a rectangular well shape and its fractional thickness of about 1.5 monolayer. [17][18][19] In this paper we aim at presenting a more detailed discussion of the optical transitions related to the existence of the wetting layer in the InAs/ GaAs QD structures, for which we use as main experimental tools the transmission electron microscopy ͑TEM͒ to deduce the composition profiles and photoreflectance spectroscopy to study the absorptionlike spectra.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…This, however, seems to remain in contradiction to some experimental observations regarding energies of the optical transitions reported by different authors, concerning, for instance, the InAs/ GaAs WL QWs. [9][10][11][12][13][14][15][16] They are very similar in many reports and are usually in satisfactory agreea͒ Author to whom correspondence should be addressed; electronic mail: grzegorz.sek@pwr.wroc.pl ment with the calculations assuming a rectangular well shape and its fractional thickness of about 1.5 monolayer. [17][18][19] In this paper we aim at presenting a more detailed discussion of the optical transitions related to the existence of the wetting layer in the InAs/ GaAs QD structures, for which we use as main experimental tools the transmission electron microscopy ͑TEM͒ to deduce the composition profiles and photoreflectance spectroscopy to study the absorptionlike spectra.…”
Section: Introductionsupporting
confidence: 50%
“…It explains both the independence of the WL QW transition energies of the growth conditions in the two InAs layers of our structure ͑the one without the InGaAs cap͒ and their almost constant values over a very broad range of different InAs/ GaAs QD structures reported in the literature. [9][10][11][12][13][14][15][16] In Fig. 6, we have summarized how the room temperature data are scattered in the published papers.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…Tuning the emission properties of QDs assemblies by in-situ annealing after changing the growth kinetics during the capping (Garcia et al, 1998, Wang et al, 2006, or by post-growth annealing under a GaAs (Leon et al, 1996;Kosogov et al, 1996;Babinski et al, 2001) or SiO 2 proximity cap (Malik et al, 1997;Xu et al, 1998;Yang et al, 2007) have been extensively reported. At the National Research Council of Canada (NRC), we have previously reported Fafard et al, 1999) a growth technique, called indium-flush, to control the size and exciton levels of the self-assembled QDs.…”
Section: Spectral Broadening Using Height Engineered Inas/gaas Quantumentioning
confidence: 99%
“…On the other hand, the structure of the SAQDs can be made uniform by a post-growth annealing. As a matter of fact, the influence of the annealing was reported using the combination of photoluminescence (PL) and transmission electron microscopy [2][3][4][5][6] . Homogeneous samples were shown to occur due to the atomic interdiffusion process between the barriers and the islands (dots) which changes the sizes and the shapes of the dots.…”
Section: Introductionmentioning
confidence: 99%